UNDERSTANDING DIFFERENT WAYS OF TEACHING READING SKILLS - Kuchkarova, Mukhabbat Yigitalievna (Educational Research in Universal Sciences, 2023)
Reading strategies known as skimming and scanning use quick eye movements and key words to quickly examine text for a variety of objectives. Reading quickly to acquire a broad picture of the content is known as skimming. Rapid reading is called scanning, and it is done to locate specific data. Scanning aids in finding a specific fact whereas skimming informs you of the overall information that is there in a section. While scanning is more like pearl diving, skimming is like snorkeling.